Factors associated with the development of renal failure among adult clients attending hospitals in Kathmandu. - Bhattarai, Sushila (2002)
ABSTRACT: This study entitled' Factors Associated with the Development of Renal Failure among Adult Clients Attending Hospitals in Kathmandu' was intended to find out the factors associated with the development of renal failure among adult clients attending hospital in Kathmandu. A case control hospital based study method renal failure (controls 65), from three tertiary level hospitals of Kathmandu, i.e. TU Teaching Hospital, Health Care Foundation Nepal-Kidney Center and Bir Hospital. Cases were selected on the basis of confirmed diagnosis of renal failure and from those attending hemodialysis treatment, where as controls were selected from those clients without renal failure admitted to the hospitals under study from Sep. 2001 to Nov. 2001. Non-probability purposive sampling techniques were used and data were collected using semi structured interview questionnaire. To maintain validity and reliability of tool literature review, consultation with experts, presenting with 10% of total sample and the modifications as needed were done. Obtained data were processed and analyzed in computer using statistical software Epi-info version 6. Mean, standard deviation, as well as odds ratio and significance level and P value were calculated to see the relationships among study variables. The analyzed data were displayed in tables, chart and graph to show the all kinds of variables. Findings revealed that, past history of medical diseases (i.e. hypertension, diabetes, kidney infection and cardiac diseases) with QR 12.82, 95% CI 5.07-33.23 P value 0.000 and use of medicines (i.e. antihypertensive, antidiabetics, antibiotics and analgesics) with QR 7.85,95% CI-3.20-19.63 P value 0.000 were found to be strongly associated with the development of renal failure. Similarly, the longer duration of smoking, than (mean +/-SD), 262.6, 157.7 months among cases, than (mean+/-SD), 226.6, 149.9 months among controls with P value 0.000 and among cases (mean +/- SD) 259.2 +/- 142.7 months than among controls (mean+/-SD) 255.8 +/- 141.7 months with P value 0.000 were also found strongly associated with the occurrence of renal failure in this study. Based on the findings this study concluded that there was strong association between the past medical diseases, use of medications, longer duration of smoking, longer duration of alcohol use and the development of renal failure in this population.